Your health service in danger (letter) - Toms, Mary
1945-02-20 1945 1940s 5 pages SOCIALIST MEDICAL ASSOCIATION 59, New Oxford Street, London, W.C.1. President: SOMERVILLE HASTINGS, M.S., F.R.C.S., L.C.C. Vice-Presidents: ALECK W. BOURNE, M.B., F.R.C.S., F.R.C.O.G. CHARLES W. BROOK, PH.D., M.A., M.R.C.S., L.R.C.P. HORACE JOULES, M.D., F.R.C.P. Prof. J.R. MARRACK, M.D., D.S.O., M.C. D. STARK MURRAY. B.Sc. M.B., CH.B. Secretary: MRS. M.L. TOMS. Hon. Treasurer: L.T. HILLIARD, M.A., M B., D.P.M. TEMPLE BAR 1632 20th February, 1945. Sir Walter Citrine, General Secretary, Trades Union Congress, Transport House, S.W.1. Dear Sir Walter, Mr. Somerville Hastings tells me that he has spoken to you about our Conference on the National Health Service; the particulars are as follows:- Date: April 15th, at 3 p.m., Place: Caxton Hall; Chairman: Mr. Hastings, Speakers: Mr. Fred Messer, M.P., and Dr. D. Stark Murray. We are inviting all trade unions to send delegates, as well as Labour Parties and Cooperative Organisations, and hope to make this a really representative national conference. I should like to take this opportunity to invite the General Council of the T.U.C. to send a representative to our Conference, although our circular is not printed yet, as I understand that they will be meeting shortly. I am enclosing a copy of the draft resolution which we shall place before the Conference, and some further 292/847/3/131